Local Money – A Response to the Globalisation of Capital? - Pacione, Michael (Quaestiones Geographicae, 2011)
In response to the global financial crisis of 2007, a number of central banks used quantitative easing to address the collapse of confidence and credit. This involved increasing the liquidity of the financial system by creating new money. It is suggested that similar strategies of ‘printing money’ in the form of local currencies may be of value for local communities confronting the challenges of economic globalisation. This paper identifies the local impacts of economic globalisation, examines the underlying causes of the global financial crisis, explains the nature of money, and illustrates the goals and different forms of local money. Finally, the potential value of local currencies as a response to the globalisation of capital is assessed.